Novel communication security scheme using dark-bright soliton conversion behaviors - Pongwongtragull, Paiboon; Teeka, Chat; Kamoldilok, Surachart; Yupapin, Preecha P. (My University, 2011)
We propose a novel scheme of communication security using dark-bright soliton conversion behaviors in which the transmission signals can be secured by using the random codes generated by dark-bright soliton conversion within the system. The system consists of two parts, where first, an optical Mach Zhender interferometer (MZI) is used to generate the coincidence dark and bright soliton pair by using the (2) phase retarder (i.e., a coupler), in which |D and |B states represent the orthogonal dark and bright soliton pulses. The signals from through (Th) port are formed and transmitted via the transmission line to the end user. Second, the adddrop filter is used to separate(filter) the required signal form the transmission link, in which the Th and drop port signals are formed as a reference and signal, respectively. In this case, we assume that both solitons are input into the MZI ports simultaneously (coincidently), in which the binary codes are randomly formed and used to present the transmission data, in which the states 0 and 1 are represented by |DB and |BD, respectively. Finally, the eavesdropper and signal accuracy are also described. © 2011 Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: communication security; dark-bright soliton conversion; orthogonal solitons; soliton communication